Pol β gap filling, DNA ligation and substrate-product channeling during base excision repair opposite oxidized 5-methylcytosine modifications - Çağlayan, Melike (DNA Repair (Amst), 2020)
DNA methylation on cytosine in CpG islands generates 5-methylcytosine (5mC), and further modification of 5mC can result in the oxidized variants 5-hydroxymethyl (5hmC), 5-formyl (5fC), and 5-carboxy (5caC). Base excision repair (BER) is crucial for both genome maintenance and active DNA demethylation of modified cytosine products and involves substrate-product channeling from nucleotide insertion by DNA polymerase (pol) β to the subsequent ligation step. Here, we report that, in contrast to the pol β mismatch insertion products (dCTP, dATP, and dTTP), the nicked products after pol β dGTP insertion can be ligated by DNA ligase I or DNA ligase III/XRCC1 complex when a 5mC oxidation modification is present opposite in the template position in vitro. A Pol β K280A mutation, which perturbates the stabilization of these base modifications within the active site, hinders the BER ligases. Moreover, the nicked repair intermediates that mimic pol β mismatch insertion products, i.e., with 3’-preinserted dGMP or dTMP opposite templating 5hmC, 5fC or 5caC, can be efficiently ligated, whereas preinserted 3’-dAMP or dCMP mismatches result in failed ligation reactions. These findings herein contribute to our understanding of the insertion tendencies of pol β opposite different cytosine base forms, the ligation properties of DNA ligase I and DNA ligase III/XRCC1 complex in the context of gapped and nicked damage-containing repair intermediates, and the efficiency and fidelity of substrate channeling during the final steps of BER in situations involving oxidative 5mC base modifications in the template strand.